Synthesis, Structural Characterization, and Evaluation of the Biological Properties of Heteroleptic Palladium(II) Complexes - Hizbullah Khan; Nek Daraz; Muhammad Nasim Khan; Muhammad Said; Nosheen Akhtar; Amin Badshah; Amir Sada Khan; Murad Ali (Bioinorganic Chemistry and Applications)
Five heteroleptic palladium(II) complexes of the general formula Pd(PR3)(tu)Cl2, where PR3 = triphenylphosphine (1), diphenyl-o-tolylphosphine (2), diphenyl-p-tolylphosphine (3), diphenyl-t-butylphosphine (4), and diphenyl-o-methoxyphenylphosphine (5), and tu = 1,3-bis(2-methoxyphenyl) thiourea. They all have been synthesized and characterized by various spectroscopic techniques (elemental analysis, FTIR, and 1H NMR and the ligand 1,3-bis(2-methoxyphenyl) thiourea was synthesized by single crystal X-ray diffraction technique). The synthesized compounds were screened for their antibacterial activity against four strains of bacteria (Escherichia coli, Shigella flexneri, Staphylococcus aureus, and Bacillus subtilis). The antitumor potential was evaluated in terms of activity against brine shrimp eggs and DNA interaction. The mixed ligand complexes have exhibited moderate antibacterial activity and promising antitumor potential.